Analisis Pengaruh Instagram terhadap Interaksi dan Kesadaran Merek pada Warung Kopi Santuy - Islamiati, Dian; Shiroth, Salman Fathy (LPPM STT Terpadu Nurul Fikri, 2025)
This study aims to investigate how marketing strategies on Instagram influence user interaction and brand awareness for Warung Kopi Santuy. The research used qualitative methods, collecting data through direct surveys of randomly selected Instagram followers. The analysis showed that active and targeted marketing on Instagram, such as posts, content types, and direct user interactions, significantly increased user interaction and brand awareness for Warung Kopi Santuy. These findings underscore the importance of effectively using social media to strengthen customer relationships and enhance brand awareness among consumers.